The upstream-downstream connection of North Atlantic and Mediterranean cyclones in semi-idealized simulations - Scherrmann, Alexander; Wernli, Heini; id_orcid:0 000-0001-9674-4837; Flaounas, Emmanouil (Copernicus, 2024)
Cyclogenesis in the Mediterranean is typically triggered by the intrusion of a potential vorticity (PV) streamer over the Mediterranean. The intrusion of the PV streamer results from a preceding Rossby wave breaking (RWB) upstream over the North Atlantic. The ridge leading to the RWB is typically amplified by the presence of warm conveyor belts (WCBs) in at least one North Atlantic cyclone about 4 d prior to Mediterranean cyclogenesis. Thus, the sequence of these four main events (namely a North Atlantic cyclone, WCBs, RWB, and the resulting PV streamers) forms an archetypal scenario leading to Mediterranean cyclogenesis. However, they rarely occur in a spatially consistent, fully repetitive pattern for real cyclone cases. To more systematically study this connection between upstream North Atlantic cyclones and Mediterranean cyclogenesis, we perform a set of semi-idealized simulations over the Euro-Atlantic domain. For these simulations, we prescribe a constant climatological atmospheric state in the initial and boundary conditions. To trigger the downstream Mediterranean cyclogenesis scenario, we perturb the climatological polar jet through the inversion of a positive upper-level PV anomaly. The amplitude of this perturbation determines the intensity of the triggered North Atlantic cyclone. This cyclone provokes RWB, the intrusion of a PV streamer over the Mediterranean, and thereby the formation of a Mediterranean cyclone. Therefore, our results show a direct connection between the presence of a North Atlantic cyclone and the downstream intrusion of a PV streamer into the Mediterranean, which causes cyclogenesis about 4 d after perturbing the polar jet. We refer to this as the upstream-downstream connection of North Atlantic and Mediterranean cyclones. To investigate the sensitivity of this connection, we vary the position and amplitude of the upper-level PV anomaly. In all simulations, cyclogenesis occurs in the Mediterranean. Nevertheless, the tracks and intensity of the Mediterranean cyclones may vary by up ...